The (un)bearable cost of European public debt sustainability - Vale, S.; Camões, F. (20th EBES conference, 2016)
The European debt crisis emerged from the 2008 financial crisis, and soon expanded to other economic dimensions. The euro area countries were caught bounded by the single currency that after integrating a set of very dissimilar economies prompted a massive transfer of credit from core to peripheral countries masking and even deepening inequalities. The recession unravelled the fragility of the European integration project, with its asymmetric accumulation of debt in a context of enlarged capital flights and the need to bail-out peripheral countries. The therapy chosen, fiscal consolidation has been to these economies as a bleeding is to an anaemic patient, decreasing growth and increasing the hurdles to recover and to drop debt-to-GDP. However, the latest decisions by the Eurogroup claim the imposition of limits to public debt as a necessary and sufficient condition to recover from the crisis and request that countries compromise on running positive budget balances to achieve it. In this paper we study European debt crisis describing the main events that took place from the creation of the single currency to 2014. We discuss how, given the recent requirements to correct fiscal unbalances and to control public debt by forcing its convergence to 60% of GDP in 20 years, the demand over already stressed countries is unsustainable, pushing the European monetary project to a debacle. To test the feasibility of the Treaty requirements in the framework of a single currency, we perform different simulations for more and less adverse scenarios based on these countries recent past performances. Our results show that the burden of debt adjustment impending over Europe is too demanding and hardly attainable, and even if the weightiest corrections will have to be taken by peripheral countries, those thought to be more solid countries will be required to run constant primary surpluses, an event without record until now.